IMPLEMENTASI NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS - Mauizatul Hasanah (JURNAL ILMIAH EDUKATIF, 2022)
This paper wants to explain the implementation of character education values ​​in social studies learning. Character education in social studies learning is the implementation of integrated character values ​​in social studies subjects with the introduction of values, gaining awareness of the importance of values ​​and internalizing values ​​in daily behavior can be grounded in the learning process. Integrated values ​​in subjects, especially the development of religious values, discipline, and environmental care. The integration of character education in the learning process starts from the stages of planning, implementing, and evaluating learning. The principles of contextual learning (contextual teaching and learning) that can be adopted in making lesson plans (design of learning activities and assessments in the syllabus, lesson plans, and teaching materials), learning processes, and evaluations.